STRETCHING LEARNING THROUGH MAPPING ACTIVITIES - THE TRANSFORMATIVE INFLUENCE OF DIALOGUE - Arniza Ghazali,; Alwani Ghazali, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
A fidgety character and an extremely low self-confidence were glaring circumstances of two learners in a first-year classroom. Mapping activities were designed for interactivity, considering the low aptitude for the English language as the instructional medium. While the fidget transformed into a focused learner upon role-play as a dialogue star in the coordinated classroom talks, the most reserved, diffident learner turned into an expressive participant. The cognitive engagement of the classroom population was evident from the significantly expanded knowledge map constructed by the students. The exploratory nature of classroom oracy drove the outcome within the dialogic space designed to engender the transformation. Space for active participation was mainly enabled by simplifying the verbal expression by extensive use of keywords in mapping. While the approach ruled out the need for correct English usage for expression of ideas, the seed map drawn by the instructor prompted learners to leave their seats to write an idea on the whiteboard. The freewill had links to the oracy that allowed for rewording and change of stance which was the primary ingredient of dialogue embedded in the mapping activities. Grafting of students’ ideas into the existing scientific concept was an essential outcome of dialogue externalised on the constructed map, driven by the dialogic space encouraging listening and thinking along the path of higher logic. The dialogic space in mapping activities and the resultant vibrant classroom of cognitively engaged participants provide evidence for designable classroom activities to uplift the immediate learning impacts.